Ethical Invasion in Islamic Religious Education Scholarships: The Influence of Funding on Academic Autonomy - Ansori, Salman Hasan; Irawan, Irawan (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2026)
Scholarship programs in Islamic religious education are generally positioned as instruments for expanding access and strengthening human resource capacity; however, the micro-ethical dimension of how funding and its accountability mechanisms shape recipients’ intellectual orientation and academic autonomy remains relatively understudied, particularly among Islamic religious education scholarship holders. This study aims to empirically test the “ethical invasion” hypothesis, namely the assumption that scholarship funding is related to the configuration of recipients’ academic autonomy. Using an explanatory quantitative approach with a cross-sectional survey design, the study involves 30 purposively selected scholarship recipients (N = 30). Data were collected through a closed-ended Likert-scale questionnaire measuring Funding Influence (X) and Academic Autonomy (Y) as composite scores (thought orientation and academic independence), covering aspects of dependence, freedom of expression, privacy and data use, values and ideology, pressure to comply, and future expectations. Data analysis employed descriptive statistics, assumption testing (Kolmogorov–Smirnov residual normality and linearity), and simple linear regression using IBM SPSS 27. The results indicate a significant regression model (F = 21.752; p < 0.001) with a relationship strength of R = 0.661 and R² = 0.437 (Adjusted R² = 0.417), showing that scholarship funding predicts meaningful variation in academic autonomy among respondents. These findings support the relevance of the “ethical invasion” hypothesis and imply the need for scholarship governance that balances accountability with the protection of academic freedom, particularly through clear limits on monitoring indicators, transparency in data approval, and secure feedback channels for recipients to safeguard autonomy in Islamic religious education contexts.